Reinterpreting Economic Growth in the Context of Global Uncertainty and Structural Transformation - Judijanto, Loso (Nomico, 2026)
This study reinterprets economic growth in the context of global uncertainty and structural transformation, emphasizing a shift from traditional GDP-oriented approaches toward multidimensional and resilience-based frameworks. Increasing global shocks such as financial crises, pandemics, and geopolitical instability have exposed the limitations of conventional growth models and necessitated a new analytical perspective. This research employs a qualitative approach using a systematic literature review of peer-reviewed journal articles and policy reports. Data are analyzed through qualitative content analysis and a thematic interpretative framework to identify key dimensions of contemporary growth. The findings reveal that economic growth is shaped by global uncertainty, structural transformation, inclusiveness, ecological sustainability, digital innovation, institutional capacity, and advanced measurement frameworks beyond GDP. The discussion highlights a paradigm shift from “more growth” to “better, resilient, and sustainable growth,” where structural policies, diversification, and innovation play central roles. The study concludes that economic growth must be understood as an adaptive, inclusive, and sustainability-oriented process that integrates economic, social, and environmental dimensions. Such an approach provides a more comprehensive basis for policy formulation in an increasingly complex global economy.